2003
DOI: 10.1103/physrevb.68.245108
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties and dynamical conductivity ofLaTiO3: From dc to optical frequencies

Abstract: We provide a complete and detailed characterization of the temperature-dependent response to ac electrical fields of LaTiO 3 , a Mott-Hubbard insulator close to the metal-insulator transition. We present combined dc, broadband dielectric, mm-wave, and infrared spectra of ac conductivity and dielectric constant, covering an overall frequency range of 17 decades. The dc and dielectric measurements reveal information on the semiconducting charge-transport properties of LaTiO 3 , indicating the importance of Ander… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 59 publications
6
41
0
Order By: Relevance
“…In the region between 3 THz and 30 THz (12.5 < log 10 ν < 13.5), resonance-like features show up, typical for phononic excitations. As was also found for other perovskite-related materials (e.g., [17,18,22]), there are three main contributions, with peaks in σ'(ν) at about 5 THz, 10 THz, and 16 THz (≈ 170 cm -1 , 330 cm -1 , and 530 cm -1 , respectively). In cubic perovskites, ABO 3 , the three infraredactive phonon excitations are ascribed to external, bending, and stretching modes.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the region between 3 THz and 30 THz (12.5 < log 10 ν < 13.5), resonance-like features show up, typical for phononic excitations. As was also found for other perovskite-related materials (e.g., [17,18,22]), there are three main contributions, with peaks in σ'(ν) at about 5 THz, 10 THz, and 16 THz (≈ 170 cm -1 , 330 cm -1 , and 530 cm -1 , respectively). In cubic perovskites, ABO 3 , the three infraredactive phonon excitations are ascribed to external, bending, and stretching modes.…”
Section: Discussionsupporting
confidence: 72%
“…its detection in the dc conductivity is consistent with our findings in the ac conductivity. VRH was also observed in various other transition metal oxides (see, e.g., [13,16,17,18,21] 6 not possible to reach a definite conclusion concerning the dimensionality of the charge transport.…”
Section: Discussionmentioning
confidence: 97%
“…Structural studies using x-ray and neutron diffraction techniques indicated a structural transition near the magnetic transition temperature, 22,23 and an optical study on LaTiO 3 showed that the additional phonon modes appeared below the magnetic transition temperature due to the structural transition. 19 However, the electronic structure and Mott gap of LaTiO 3 hardly changed with temperature. The behavior of ͑ ͒ in LaTiO 3 is quite distinguished from that of Sr 2 IrO 4 , where ͑ ͒ of Sr 2 IrO 4 showed strong temperature dependence without a structural transition.…”
Section: Resultsmentioning
confidence: 99%
“…To exemplify this point, we consider the expectation value of H M , expressed in terms of the angles and , and, by the symmetries of the sublattice couplings, in terms of the couplings between the sublattice bonds ij = 12 and 13, 2 , and sin sin which are also of order 2 ͒, and the 2 correction of D 13 Dx ͑which is multiplied by sin sin ͒. Those contributions have been excluded from our calculation of the canting angles.…”
Section: A the Magnetic Order Of The Classical Ground Statementioning
confidence: 99%
“…12 The presence of orbital order at low temperatures has also been concluded from measurements of the dielectric properties and the dynamical conductivity. 13 Furthermore, an orbital contribution to the specific heat, which is predicted by the orbitalliquid model, has not been found in experiment. 14 Hence from the recent experiments it must be concluded that the orbital-liquid model is inappropriate for LaTiO 3 .…”
Section: Introductionmentioning
confidence: 99%